2011
DOI: 10.1200/jco.2010.30.9799
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up Analysis of HD9601 Trial Comparing ABVD Versus Stanford V Versus MOPP/EBV/CAD in Patients With Newly Diagnosed Advanced-Stage Hodgkin's Lymphoma: A Study From the Intergruppo Italiano Linfomi

Abstract: The long-term analysis confirmed ABVD and MEC superiority to StV. The use of RT after StV was established as mandatory. ABVD is still to be considered as the standard treatment with a good balance between efficacy and toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 17 publications
0
33
0
Order By: Relevance
“…13 Here, we report the results of a prospective, randomized, multicenter trial that compared ABVD and SV in advanced-stage HL. 12 The 5-year FFS was significantly lower for patients treated with SV (54%) compared with ABVD (78%) and MEC (81%).…”
Section: Journal Of Clinical Oncologymentioning
confidence: 99%
“…13 Here, we report the results of a prospective, randomized, multicenter trial that compared ABVD and SV in advanced-stage HL. 12 The 5-year FFS was significantly lower for patients treated with SV (54%) compared with ABVD (78%) and MEC (81%).…”
Section: Journal Of Clinical Oncologymentioning
confidence: 99%
“…2 In contrast, the prognosis of the remaining patients who relapse or fail to make complete remission, and in stage III and IV patients, is relatively poor. [3][4][5][6][7][8][9] In addition, patients who achieve long-term disease-free survival frequently have infertility and secondary malignancies, including breast cancer and cardiac failure, which are related to chemotherapeutic agents and radiation therapies. [10][11][12] Therefore, the development of new therapeutic strategies is necessary to improve clinical outcome and reduce the long-term side effects of current treatments in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Four studies showed interim FDG-PET-negative patients after two cycles of ABVD to have an excellent PFS ranging between 92% and 95% (19,20,25,29) (Table 3). However, other studies in similar settings and with similar patient spectra reported PFS rates ranging between 81% and 85.5% (28,30,31,33), which can be considered rather poor regarding the a priori PFS (without taking into account the interim FDG-PET results) of approximately 75% (3)(4)(5)(6). Aforementioned findings underline that a negative interim FDG-PET result cannot exclude residual disease, which is inherent to its limited spatial resolution (34).…”
mentioning
confidence: 90%